2024
DOI: 10.3389/fcell.2023.1332205
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-9 in cancer therapy: from immune checkpoint ligand to promising therapeutic target

Minpu Zhang,
Cun Liu,
Ye Li
et al.

Abstract: Galectin-9 (Gal-9) is a vital member of the galectin family, functioning as a multi-subtype galactose lectin with diverse biological roles. Recent research has revealed that Gal-9’s interaction with tumors is an independent factor that influences tumor progression. Furthermore, Gal-9 in the immune microenvironment cross-talks with tumor-associated immune cells, informing the clarification of Gal-9’s identity as an immune checkpoint. A thorough investigation into Gal-9’s role in various cancer types and its int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 124 publications
0
0
0
Order By: Relevance
“…According to reports, LGALS9 binds to Tim-3 and induces apoptosis by inducing T-helper 1 cell death via intracellular calcium current. Thus, this leads to induction of immune tolerance and inhibition of T-helper 1 and T-helper 17 cells responses [ 56 ]. It was demonstrated that inhibiting the LGALS9 /Tim-3 pathway elicits anti-tumor immune responses and hampers the development of tumors [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to reports, LGALS9 binds to Tim-3 and induces apoptosis by inducing T-helper 1 cell death via intracellular calcium current. Thus, this leads to induction of immune tolerance and inhibition of T-helper 1 and T-helper 17 cells responses [ 56 ]. It was demonstrated that inhibiting the LGALS9 /Tim-3 pathway elicits anti-tumor immune responses and hampers the development of tumors [ 57 ].…”
Section: Discussionmentioning
confidence: 99%